All-cause hospitalization according to demographic group in people living with HIV in the current antiretroviral therapy era. (2nd February 2021) - Rein, Sophia M.; Lampe, Fiona C.; Johnson, Margaret A.; Bhagani, Sanjay; Miller, Robert F.; Chaloner, Clinton; Phillips, Andrew N.; Burns, Fiona M.; Smith, Colette J.
Abstract : Objective: We investigated differences in all-cause hospitalization between key demographic groups among people with HIV in the UK in the current antiretroviral therapy (ART) era. Design/Methods: We used data from the Royal Free HIV Cohort study between 2007 and 2018. Individuals were classified into five groups: MSM, Black African men who have sex with women (MSW), MSW of other ethnicity, Black African women and women of other ethnicity. We studied hospitalizations during the first year after HIV diagnosis (Analysis-A) separately from those more than one year after diagnosis (Analysis-B). In Analysis-A, time to first hospitalization was assessed using Cox regression adjusted for age and diagnosis date. In Analysis-B, subsequent hospitalization rate was assessed using Poisson regression, accounting for repeated hospitalization within individuals, adjusted for age, calendar year, time since diagnosis. Results: The hospitalization rate was 30.7/100 person-years in the first year after diagnosis and 2.7/100 person-years subsequently; 52% and 13% hospitalizations, respectively, were AIDS-related. Compared with MSM, MSW and women were at much higher risk of hospitalization during the first year [aHR (95% confidence interval, 95% CI): 2.7 (1.7–4.3), 3.0 (2.0–4.4), 2.0 (1.3–2.9), 3.0 (2.0–4.5) for Black African MSW; other ethnicity MSW; Black African women; other ethnicity women respectively, Analysis-A] and remained at increased risk subsequently [corresponding aIRR (95% CI): 1.7 (1.2–2.4), 2.1 (1.5–2.8), 1.5 (1.1–1.9), 1.7 (1.2–2.3), Analysis-B]. Conclusion: In this setting with universal healthcare, substantial variation exists in hospitalization risk across demographic groups, both in early and subsequent periods after HIV diagnosis, highlighting the need for targeted interventions. Abstract : Supplemental Digital Content is available in the text